T-Duality of Open Strings. M-Theory and the Duality Web - Năstase, Horaţiu [UNESP] (My University, 2019)
In the last chapter, we considered T-duality for closed strings. Now we start off by considering T-duality for open strings, and see that it will lead to D-branes. Then, we define the low energy supergravity limits of string theory, the strong coupling limit of string theory known as M-theory, and finally show that all the various incarnations of string theory are related into a single duality web, as facets of the same unique theory.